The Democratic Republic of Congo between hope and despair - Deibert, Michael (London Zed Books, 2013)
Over the past two decades, the Democratic Republic of Congo has been at the centre of the deadliest series of conflicts since the Second World War, and now hosts the largest United Nations peacekeeping mission in the world. In this compelling book, acclaimed journalist Michael Deibert paints a picture of a nation in flux, inching towards peace but at the same time solidifying into another era of authoritarian rule under its enigmatic president, Joseph Kabila.
Includes bibliographical references (pages 209-242) and index.
Keywords: Congo (Democratic Republic) --History --1997-